Coastal Women's Contribution to Child Stunting Prevention: A Social Dimension Approach in Coastal Communities - Askar, Hardianty (Jurnal Perikanan dan Kelautan, 2025)
Stunting is a serious health issue that affects children's physical and mental development, with both short-term and long-term harmful impacts. This study aims to examine the influence of social aspects of women in coastal areas on stunting prevention, focusing on the role of fisheries product diversification. Data were collected through observation, interviews, and questionnaire responses from three groups of mothers: mothers of toddlers, pregnant mothers, and breastfeeding mothers. Data analysis using a quantitative approach through multiple regression analysis shows that for mothers of toddlers, variables such as parental education level, fish consumption patterns, early marriage rates, availability of health facilities, and the role of fisheries product diversification significantly impact stunting prevention. For pregnant mothers, considerable influence was found on the availability of health facilities and the role of fisheries product diversification. Breastfeeding mothers, variables like parental education level, child-rearing patterns, fish consumption patterns, and the availability of health facilities showed significant effects. The results of this study are expected to contribute to developing more effective and integrated health policies, particularly in stunting prevention in coastal communities.